2019
DOI: 10.3906/vet-1812-59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body condition score on nutritional diseases and milk yield in dairy cattle

Abstract: The purpose of this study is to examine the effects of body condition score (BCS) on nutritional diseases and milk yield in dairy cattle. Fifty-nine randomly selected Holstein Friesian cattle, lactation numbers 3-6, were used in this study from a total of 350 dairy cattle in the establishment. All of the cows in the study were fed with the same total mixed ration (TMR), and BSC was determined by inspection and palpation in the first 5 days after calving. The cows were separated into two groups according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Compared to BCS1 group of cows, which recorded an average body weight of 381.23 ± 2.48 kg, and at peak of lactation it reached 374.70 ± 2.01 kg, with an average weight change of -26.53 ± 0.70 kg (6.95%). The results of the current study were similar to the findings of previous studies, as it found an effect of the body condition score prepartum on the energy reserves, which was reflected in the body weight at calving, as well as in the amount of weight loss postpartum, as the cows with the lowest body condition scor (4 points) were Less (P< 0.001) in weight than the cows with the highest body condition scor (5 points) by 54 kg one week prepartum, and remained less (P< 0.001) during twelve weeks from the start of lactation, but the amount of the difference decreased to 15 kg At the twelfth week of lactation, since the amount of postpartum weight loss is less in cows with a lower body condition scor, and they recover faster compared to cows with a higher body condition scor [20], This may be attributed to higher dry matter intake by lower body condition scor cows and lower exposure to metabolic stress [21,22]. While other studies indicated no associations between weight and body condition scor [23], or low associations [24], while others confirmed the existence of moderate associations [25], or high associations [13], while it was stated [14] The relationship between body weight and body condition scor is linear, and therefore a large part of the variation in body weight can be explained by body condition scor because body weight increases with body condition scor.…”
Section: Body Condition (Bcs) Relationship To the Average Body Weight...mentioning
confidence: 91%
“…Compared to BCS1 group of cows, which recorded an average body weight of 381.23 ± 2.48 kg, and at peak of lactation it reached 374.70 ± 2.01 kg, with an average weight change of -26.53 ± 0.70 kg (6.95%). The results of the current study were similar to the findings of previous studies, as it found an effect of the body condition score prepartum on the energy reserves, which was reflected in the body weight at calving, as well as in the amount of weight loss postpartum, as the cows with the lowest body condition scor (4 points) were Less (P< 0.001) in weight than the cows with the highest body condition scor (5 points) by 54 kg one week prepartum, and remained less (P< 0.001) during twelve weeks from the start of lactation, but the amount of the difference decreased to 15 kg At the twelfth week of lactation, since the amount of postpartum weight loss is less in cows with a lower body condition scor, and they recover faster compared to cows with a higher body condition scor [20], This may be attributed to higher dry matter intake by lower body condition scor cows and lower exposure to metabolic stress [21,22]. While other studies indicated no associations between weight and body condition scor [23], or low associations [24], while others confirmed the existence of moderate associations [25], or high associations [13], while it was stated [14] The relationship between body weight and body condition scor is linear, and therefore a large part of the variation in body weight can be explained by body condition scor because body weight increases with body condition scor.…”
Section: Body Condition (Bcs) Relationship To the Average Body Weight...mentioning
confidence: 91%
“…The results of [74] indicated that there was a significant increase in ketosis in cows with a body condition of 4-5 points compared to cows with a body condition of 3-4 points and cows with a body condition of 2-3 points according to the 1-5 points scal. [75] in his study on the diagnosis of some cases of ketosis in milk cows with a body condition > 3 points, and the risk of ketosis increases when the body condition is ≥ 3.75 points at entering the dry period and at calving. While previous studies indicated that there was no significant relationship or effect of the state of the body in ketosis [76,77].…”
Section: Relationship Of Body Condition Score (Bcs) With Some Patholo...mentioning
confidence: 99%